4-Chlorbenzoyl Berbamine, a Novel Derivative of the Natural Product Berbamine, Potently Inhibits the Growth of Human Myeloma Cells by Modulating the NF-κB and JNK Signalling Pathways. (25th November 2016) - Liang, Yun; He, Xin; Li, Xian; Zhang, Xuzhao; Zhang, Xiaohong; Zhang, Lei; Qiu, Xi; Zhao, Xiaoying; Xu, Rongzhen
ABSTRACT: Multiple myeloma (MM) remains incurable despite the development and the use of new agents. In our studies, we found that 4-chlorbenzoyl berbamine (BBMD9), a novel synthetic derivative of berbamine, inhibited the proliferation of MM cells in dose- and time-dependent manners. Flow cytometric (FCM) analysis revealed that MM cells were arrested in the G1 phase and that apoptotic cells increased in a time-dependent manner. Moreover, the BBMD9 treatment downregulated IKKα and IKKβ, inhibited p-IκBα, and blocked p65 nuclear localization. Consistently, NF-κB downstream targets, such as cyclinD1 and survivin, were also reduced. In addition, BBMD9 phosphorylated the activity of JNK and c-Jun.